Analisis Kesulitan Belajar Matematika (Diskalkulia) bagi Anak Berkebutuhan Khusus - Septy Nurfadhillah; Dian Chaerani Utami; Indah Aprianti; Widya Nur Aini; Dhita Safitri; Indah Ayu Anggraini; Dian Andriani Suherdi; Siti Khoiriah (Jurnal Halaqah, 2022)
This study aims to describe the difficulties of children with special mathematical needs. This research is qualitative. Data were collected by observation, interview, and documentation methods. The analysis technique uses observation, interview and documentation methods. From the results of the study, it was found that the cause of learning difficulties in mathematics for children with special needs was because the learning design, learning methods, learning media and the use of language in special mathematics learning in inclusive classes were not perfect.